The Influence of Time Management on Teacher Performance at UPT SMA Negeri 6 Sinjai, West Sinjai District, Sinjai Regency - Mutmainnah; Samsul Rizal; Sri Andayaningsih (Pustaka Digital Indonesia, 2024)
This research aims to examine the effect of time management on teacher performance at UPT SMA Negeri 6 Sinjai, West Sinjai District, Sinjia Regency. The type of research used in this research is a quantitative survey method. The teacher sample consisted of 41 samples selected using non-probability sampling through saturated sampling techniques. The data in the sample uses primary data obtained using a distributed questionnaire. The data analysis methods used are validity test, reliability test, classical assumption test, simple linear regression test, statistical test and hypothesis test using the SPSS 25 analysis tool. Based on the research results, partially time management (X) shows a tcount value of 0.778 > ttable 0.3081 means that there is a positive and significant influence of time management (X) on teacher performance (Y). This is proven by a significant value of 0.000 < 0.05 with a coefficient of determination (R Square) of 61.5% and the remaining 38.5% is influenced by things that have not been examined in this research.